Implementasi Pernyataan Standar Akuntansi Keuangan No 45 Pada Panti Asuhan Al-Huda Ridwaniyah - Jumaiyah, Jumaiyah; Wahidullah, Wahidullah; Jumaiyah, Jumaiyyah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
The purpose of this study is to find out whether the nonprofit organization implements financial statements in accordance with Statement of Financial Accounting Standards (PSAK 45) on financial reporting of nonprofit organizations. This research uses descriptive qualitative method. taking data using observation, interviews, and documentation. Direct observation was conducted on the subject of research with the knowledge of the board and without the knowledge of the board, the interview was done to the Orphanage management, while the documentation was taken from the financial report data which is owned by the board. The results of this study indicate that the orphanage compiles the activity report and the statement of financial position at the end of the period. While cash flow and notes reports on financial statements (CaLK) have not yet been compiled. Suggestions from this study orphanage should prepare a complete financial report in accordance with PSAK 45. Keywords: orphanage, PSAK number.45, non-profit, financial report